Analytic integrability inside a family of degenerate centers. (October 2016) - Algaba, Antonio; Checa, Isabel; García, Cristóbal; Giné, Jaume
Abstract: In this paper we study the analytic integrability around the origin inside a family of degenerate centers or perturbations of them. For this family analytic integrability does not imply formal orbital equivalence to a Hamiltonian system. It is shown how difficult is the integrability problem even inside this simple family of degenerate centers or perturbations of them.